Immunotherapy targeting pyroglutamate-3 Aβ: prospects and challenges. Issue 1 (December 2016) - Cynis, Holger; Frost, Jeffrey; Crehan, Helen; Lemere, Cynthia
Abstract Immunization against amyloid-β (Aβ) peptides deposited in Alzheimer's disease (AD) has shown considerable therapeutic effect in animal models however, the translation into human Alzheimer's patients is challenging. In recent years, a number of promising Aβ immunotherapy trials failed to reach primary study endpoints. Aside from uncertainties in the selection of patients and the start and duration of treatment, these results also suggest that the mechanisms underlying AD are still not fully understood. Thorough characterizations of protein aggregates in AD brain have revealed a conspicuous heterogeneity of Aβ peptides enabling the study of the toxic potential of each of the major forms. One such form, amino-terminally truncated and modified pyroglutamate (pGlu)-3 Aβ peptide appears to play a seminal role for disease initiation, qualifying it as novel target for immunotherapy approaches.